Radiolabeling of Human Serum Albumin With Terbium-161 Using Mild Conditions and Evaluation of in vivo Stability - Cassells, Irwin; Ahenkorah, Stephen; Burgoyne, Andrew R.; Van de Voorde, Michiel; Deroose, Christophe M.; Cardinaels, Thomas; Bormans, Guy; Ooms, Maarten; Cleeren, Frederik (Frontiers in Medicine, 2021)
Targeted radionuclide therapy (TRNT) is a promising approach for cancer therapy. Terbium has four medically interesting isotopes (149Tb, 152Tb, 155Tb and 161Tb) which span the entire radiopharmaceutical space (TRNT, PET and SPECT imaging). Since the same element is used, accessing the various diagnostic or therapeutic properties without changing radiochemical procedures and pharmacokinetic properties is advantageous. The use of (heat-sensitive) biomolecules as vector molecule with high affinity and selectivity for a certain molecular target is promising. However, mild radiolabeling conditions are required to prevent thermal degradation of the biomolecule. Herein, we report the evaluation of potential bifunctional chelators for Tb-labeling of heat-sensitive biomolecules using human serum albumin (HSA) to assess the in vivo stability of the constructs. p-SCN-Bn-CHX-A´´-DTPA, p-SCN-Bn-DOTA, p-NCS-Bz-DOTA-GA and p-SCN-3p-C-NETA were conjugated to HSA via a lysine coupling method. All HSA-constructs were labeled with [161Tb]TbCl3 at 40 °C with radiochemical yields higher than 98%. The radiolabeled constructs were stable in human serum up to 24 hours at 37 °C. 161Tb-HSA-constructs were injected in mice to evaluate their in vivo stability. Increasing bone accumulation as a function of time was observed for [161Tb]TbCl3 and [161Tb]Tb-DTPA-CHX-A´´-Bn-HSA, while negligible bone uptake was observed with the DOTA, DOTA-GA and NETA variants over a 7-day period. The results indicate that the p-SCN-Bn-DOTA, p-NCS-Bz-DOTA-GA and p-SCN-3p-C-NETA are suitable bifunctional ligands for Tb-based radiopharmaceuticals, allowing for high yield radiolabeling in mild conditions.